Doxycycline in the management of sexually transmitted infections. (22nd November 2017) - Peyriere, Hélène; Makinson, Alain; Marchandin, Hélène; Reynes, Jacques
Abstract: Doxycycline is a second-generation tetracycline, available worldwide for half a century. It is an inexpensive broad-spectrum antimicrobial agent largely used in the management of several bacterial infections, particularly involving intracellular pathogens, as well as in the treatment of acne or for the prophylaxis of malaria. Physicochemical characteristics of doxycycline (liposolubility) allow a high diffusion in the tissues and organs. It has high bioavailability and a long elimination half-life allowing oral administration of one or two daily doses. Over the last decade, the prevalence of bacterial sexually transmitted infections (STIs) (syphilis, chlamydiosis, gonorrhoea and Mycoplasma genitalium infections) has increased in most countries, mainly in MSM, many of whom are infected with HIV. In light of increasing prevalence of resistance towards first-line regimens of some STI agents and recently updated recommendations for STI management, doxycycline appears to be an attractive option compared with other available antibiotics for the treatment of some STIs due to its efficacy, good tolerability and oral administration. More recently, indications for doxycycline in STI prophylaxis have been evaluated. Considering the renewed interest of doxycycline in STI management, this review aims to update the pharmacology of, efficacy of, safety of and resistance to doxycycline in this context of use.